Chondrogenic Potential of Human Dental Pulp Stem Cells Cultured as Microtissues - Rubén Salvador-Clavell; José Javier Martín de Llano; Lara Milián; María Oliver; Manuel Mata; Carmen Carda; María Sancho-Tello (Hindawi Limited, 2021)
Several tissue engineering stem cell-based procedures improve hyaline cartilage repair. In this work, the chondrogenic potential of dental pulp stem cell (DPSC) organoids or microtissues was studied. After several weeks of culture in proliferation or chondrogenic differentiation media, synthesis of aggrecan and type II and I collagen was immunodetected, and SOX9, ACAN, COL2A1, and COL1A1 gene expression was analysed by real-time RT-PCR. Whereas microtissues cultured in proliferation medium showed the synthesis of aggrecan and type II and I collagen at the 6th week of culture, samples cultured in chondrogenic differentiation medium showed an earlier and important increase in the synthesis of these macromolecules after 4 weeks. Gene expression analysis showed a significant increase of COL2A1 after 3 days of culture in chondrogenic differentiation medium, while COL1A1 was highly expressed after 14 days. Cell-cell proximity promotes the chondrogenic differentiation of DPSCs and important synthesis of hyaline chondral macromolecules.